Epistemologi Hukum Islam: Perspektif Historis, Sosiologis dalam Pengembangan Dalil - Asmawi, Asmawi (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2021)
The epistemology of Islamic law that deals with the development of arguments, applies dynamically, since the application of Islamic law itself, from the time of the Prophet to the present. In the early days of Islam epistemology was developed based on revelation and reason. Along with the golden age of Islam, various reasons and methods of discovery of Islamic law developed such as qiyas, istislah, urf, istishab. In modern times, the dynamics have also become increasingly complex with the increasingly complex problematics of Islamic law, and the latter is using assistive sciences in the discovery of Islamic law. Such as the science of sociology, astronomy, health, biology, medicine, chemistry, and others. So that the epistemology of Islamic law is rationalist, empirical, theologic, and phenomenological.